Heat transfer enhancement of a circular tube heat exchanger fitted with an elliptic shaped turbulator designed in the context of developing countries. (25th April 2015) - Rivier, Michel; Sébastian, Patrick; Goli, Thierry; Raffray, Guilhem; Collignan, Antoine
Abstract: Energy availability, heat conversion and transfer still represent an impediment to the food processing sector in developing countries. Optimisation of tubular heat exchangers remains a concern for equipment designers and manufacturers. This work assesses the performances of a turbulator in terms of heat transfer and fluid friction characteristics in a heat exchanger tube. The turbulator is designed based on an elliptic shape suited to be made locally. The geometric dispersions caused by this kind of manufacturing process were surveyed, and then considered in the study. Hence 26 turbulators, manufactured with or without geometric dispersions, and with 45° or 60° ellipses, were tested in three tubes of different diameters. To ensure the closest possible resemblance to actual applications, the tests were carried out using air as a working fluid, with a low range of Reynolds number (1700–8000 for heat transfer and 3000 to 16, 000 for friction factor). The heat transfer rate in a tube fitted with a turbulator may be increased up to 900%, in turbulent flow and with a curve angle of 45°. On the flip side, there is a very big pressure drop. However, a surface-based dispersion of 30% which could be generated by local manufacturing leads to a 50% reduction in the friction factor, but only a 20% reduction in the Nusselt number. The models obtained will enable a multi-criteria analysis for heat exchanger optimisation in a context specific to developing countries. Highlights: In developing countries, manufacture dispersions impact heat exchanger efficiency. Effects of turbulator design variables on heat transfer and pressure drop are studied. Nusselt number is predicted as a function of turbulator design variables. Fanning friction factor is also predicted through the same design variables. Surface-based dispersion was found to have the most impact on exchanger performance.